Diagnostics of timing noise in middle-aged pulsars. Issue 4 (19th June 2019) - Namkham, Nakornping; Jaroenjittichai, Phrudth; Johnston, Simon
ABSTRACT: Radio pulsars are often used as clocks in a wide variety of experiments. Imperfections in the clock, known as timing noise, have the potential to reduce the significance of, or even thwart e.g. the attempt to find a stochastic gravitational wave (GW) background. We measure the timing noise in a group of 129 mostly middle-aged pulsars (i.e. characteristic ages near 1 Myr) observed with the Parkes radio telescope on a monthly basis since 2014. We examine four different metrics for timing noise, but it remains unclear which, if any, provides the best determination. In spite of this, it is evident that these pulsars have significantly less timing noise than their younger counterparts, but significantly more than the (much older) millisecond pulsars (MSPs). As with previous authors, we find a strong correlation between timing noise and the pulsar spin-down rate, $\dot{ν}$ . However, for a given $\dot{ν}$ there is a spread of about a factor of 30 in the strength of the timing noise likely indicating that nuclear conditions in the interior of the stars differ between objects. We briefly comment on the implications for GW detection through pulsar timing arrays as the level of timing noise in MSPs may be less than predicted.